Soybean seed yield in relation to soil fertility management - Conterato, Milton J.D.; Costa, José Antonio (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were performed at the EEA/UFRS, Guaíba, RS, in a São Jerônimo (Ultisol, Paleudult) type, soil during the 1981/82 growing season. Soybean (Glycine max (L.) Merrill) cultivars Ivorá, Planalto, Década, BR-4, União, LC 72-749, BR-3, lvaí Hardee and Cobb were tested, with and without maintenance fertilization. Irrigation was used to provide and environment for high grain yield production. Without irrigation the-yield levels attained were the normal for the year, with good management. Without irrigation, there was no difference between fertilized and not fertilized plots, in a year with water stress. When moisture was not limiting, even with high levels of P and K, in the average, the yields with fertilization increased by 195 kg/ha. There was significant difference among cultivars with and without irrigation. BR-4, Cobb, Hardee and Ivaí had the highest seed yield in all situations. The results showed that, in a soil similar to the one utilized once limed and corrected for P and K, in a way that the nutrient levels have reached or are above the critical levels, its possible to reduce the maintenance fertilization, at least for one year, since the crop grown during the winter had received the recommended maintenance fertilization.